2019
DOI: 10.1016/j.athoracsur.2019.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Patients Undergoing Cardiothoracic Surgery for Infective Endocarditis

Abstract: Background. This study aimed to identify risk factors associated with mortality of patients who undergo cardiac surgery for infective endocarditis.Methods. A retrospective review was performed of patients with infective endocarditis who underwent cardiac surgery at a quaternary Australian hospital between 2004 and 2014. Patient data were collected and prospectively analyzed.Results. In all, 465 patients underwent surgery during the study period, with 30 deaths (6.45%). Factors independently associated with in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, valve surgery in the setting of IE is often more complicated than in non-IE pathologies due to multiple valves being affected by IE and the fragility of infected tissues. Thus, adding CABG to such complex surgeries prolongs the duration of CPB and aortic cross clamp times which are known independent predictors of perioperative mortality in patients undergoing cardiac surgery for non-IE [10], as well as for IE [11,12]. In our study, concomitant CABG was indeed associated with longer CPB and cross-clamp durations, and higher in-hospital mortality in the overall patient population.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In addition, valve surgery in the setting of IE is often more complicated than in non-IE pathologies due to multiple valves being affected by IE and the fragility of infected tissues. Thus, adding CABG to such complex surgeries prolongs the duration of CPB and aortic cross clamp times which are known independent predictors of perioperative mortality in patients undergoing cardiac surgery for non-IE [10], as well as for IE [11,12]. In our study, concomitant CABG was indeed associated with longer CPB and cross-clamp durations, and higher in-hospital mortality in the overall patient population.…”
Section: Discussionsupporting
confidence: 57%
“…The main cause of death in IE is septic multi-organ failure, which is more likely to occur if clamp and bypass times are long [3,[7][8][9]. Adding CABG to valve surgery prolongs the duration of the cardiopulmonary bypass (CPB) and aortic cross-clamping [10][11][12][13]. In addition, the prognostic impact of adding CABG to valve surgery has even been questioned for non-IE patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From our data, an in-hospital mortality of 20.3% was identified among patients ≥75 years [ 34 ]. A single-center study from Australia, investigated 465 patients undergoing cardiac surgery for IE and found, among other factors, that increasing age, active bacterial endocarditis, and a high European System for Cardiac Operative Risk Evaluation score were associated with an increased risk of in-hospital mortality [ 35 ]. A previously mentioned Spanish study with data from tertiary centers concluded that age was not an independent predictor of in-hospital mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that patients ≥75 years who underwent surgery, the in-hospital and 90-day mortality was tripled compared with patients < 60 years. Several risk-scores have been developed to predict in-hospital mortality in patients with IE with an indication for surgery and age constitutes an important parameter in these risk scores [17][18][19][20]33] [35]. A previously mentioned Spanish study with data from tertiary centers concluded that age was not an independent predictor of in-hospital mortality [36].…”
Section: Mortality By Age Groupsmentioning
confidence: 99%
“…16 A number of risk factors predict outcome in infective endocarditis, especially when surgical treatment is indicated. Patient-and disease-related factors as well as infective endocarditis-mediated complications increasing the risk of mortality have been described 16,20,[56][57][58][59][60][61][62][63][64][65][66] (table 3). The abundance of such risk factors may lead to poor prognosis, and due to the inability to withstand the surgical hit, this could be a reason to avoid surgery.…”
Section: Prediction Of Outcomementioning
confidence: 99%